Mining for natural product antileishmanials in a fungal extract library. (December 2019) - Mbekeani, A.J.; Jones, R.S.; Bassas Llorens, M.; Elliot, J.; Regnault, C.; Barrett, M.P.; Steele, J.; Kebede, B.; Wrigley, S.K.; Evans, L.; Denny, P.W.
Abstract: Leishmaniasis is a Neglected Tropical Disease caused by the insect-vector borne protozoan parasite, Leishmania species. Infection affects millions of the World's poorest, however vaccines are absent and drug therapy limited. Recently, public-private partnerships have developed to identify new modes of controlling leishmaniasis. Most of these collaborative efforts have relied upon the small molecule synthetic compound libraries held by industry, but the number of New Chemical Entities (NCE) identified and entering development as antileishmanials has been very low. In light of this, here we describe a public-private effort to identify natural products with activity against Leishmania mexicana, a causative agent of cutaneous leishmanaisis (CL). Utilising Hypha Discovery's fungal extract library which is rich in small molecule (<500 molecular weight) secondary metabolites, we undertook an iterative phenotypic screening and fractionation approach to identify potent and selective antileishmanial hits. This led to the identification of a novel oxidised bisabolane sesquiterpene which demonstrated activity in an infected cell model and was shown to disrupt multiple processes using a metabolomic approach. In addition, and importantly, this study also sets a precedent for new approaches for CL drug discovery. Graphical abstract: Image 1